Análise comparativa de alternativas para pavimentação de rodovias: pavimento flexível x pavimento rígido - Costa, Jochezan da Silva (2013)
By having lower initial cost compared to rigid pavement, the pavement turns out to be more flexible employee, while the rigid pavement is still little used to have, but a higher initial cost, the stigma of being related only very intense traffic. The evaluation of the advantages of choosing between flexible pavement and rigid pavement will be the target of this work. As I stand before this choice the road engineer has a complex decision to be taken, which is the research problem of this study. The research, through a methodology of a character essentially theoretical / bibliographic, seeks to identify the most recommended uses for each type of flooring cited, as well as the costs associated with the deployment and maintenance during the project period. Aims at analyzing the technical characteristics of these two types of flooring, as well as costs associated with the deployment of the same, since the building of the pavement until the end of the project period considered, indicating the end, the most appropriate use for each type of flooring and its constraints and technical limitations. It was concluded that the paving rigid compared to the flexible, has better cost-effective due to the low need for maintenance during the lifetime. Also that the methods and data characteristics compared, the rigid pavement is presented as a more reliable and more sophisticated formulation.